Knowledge domain and emerging trends in empagliflozin for heart failure: A bibliometric and visualized analysis - Zhang, Xuesong; Zhang, Ying; Hu, Yuanhui (Frontiers in Cardiovascular Medicine, 2022)
Abstract: Objective: Empagliflozin, a sodium-glucose cotransporter 2 inhibitor (SGLT2i), is recommended for all patients with Heart failure (HF) to reduce the risk of Cardiovascular death, hospitalization, and HF exacerbation. Qualitative and quantitative evaluation was conducted by searching relevant literatures of Empagliflozin for Heart Failure from 2013 to 2022, and visual analysis in this field was conducted. Methods: The data were from the Web of Science Core Collection database (WOSCC). The bibliometric tools, CiteSpace and VOSviewer, were used for econometric analysis to probe the evolvement of disciplines and research hotspots in the field of Empagliflozin for Heart Failure. Results: A total of 1461 literatures with 43861 references about Empagliflozin for Heart Failure in the decade were extracted from WOSCC, and the number of manuscripts were on a rise. In the terms of co-authorship, USA leads the field in research maturity and exerts a crucial role in the field of Empagliflozin for Heart Failure. Multidisciplinary research is conducive to future development. With regards to literatures, we obtained 9 hot paper, 93 highly cited literatures and 10 co-cited references. The current research focuses on the following three aspects: Empagliflozin improves left ventricular remodeling, exert renal protection, and increases heart rate variability.Conclusion: Based on methods such as bibliometrics, citation analysis and knowledge graph, this study analyzed the current situation and trend of Empagliflozin for Heart Failure, sorted out the knowledge context in this field, and provided reference for current and future prevention and scientific research.